2006
DOI: 10.1007/s00248-006-9062-8
|View full text |Cite
|
Sign up to set email alerts
|

Three-dimensional Microorganization of the Soil–Root–Microbe System

Abstract: Soils contain the greatest reservoir of biodiversity on Earth, and the functionality of the soil ecosystem sustains the rest of the terrestrial biosphere. This functionality results from complex interactions between biological and physical processes that are strongly modulated by the soil physical structure. Using a novel combination of biochemical and biophysical indicators and synchrotron microtomography, we have discovered that soil microbes and plant roots microengineer their habitats by changing the poros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
141
0
3

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 236 publications
(155 citation statements)
references
References 23 publications
8
141
0
3
Order By: Relevance
“…On golf course soils, York and Canaway (2000) showed a direct link between the presence of basidiomycetes fungi and the development of fairy rings. Feeney et al (2006a) found a strong relationship between fungal biomass and water repellency in an agricultural soil. However, this could not be simulated in a study that controlled fungal biomass with biocides in the laboratory (Feeney et al 2006b).…”
Section: Review Soil and Water Res 3 2008 (Special Issue 1): S21-s29mentioning
confidence: 90%
“…On golf course soils, York and Canaway (2000) showed a direct link between the presence of basidiomycetes fungi and the development of fairy rings. Feeney et al (2006a) found a strong relationship between fungal biomass and water repellency in an agricultural soil. However, this could not be simulated in a study that controlled fungal biomass with biocides in the laboratory (Feeney et al 2006b).…”
Section: Review Soil and Water Res 3 2008 (Special Issue 1): S21-s29mentioning
confidence: 90%
“…Soil fungi may influence abiotic properties of their environment through the production or decomposition of hydrophilic and hydrophobic organic compounds that influence water transport and retention (Feeney et al, 2006;Czarnes et al, 2000;Roper, 2004). These processes will affect water availability to plants and microbes, pollutant transport through bypass flow, rainfall infiltration and overland runoff, and the stability of the soil structure by reducing slaking stresses imposed by rapid wetting (Hallett & Young, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the impact of soil moisture, plant species and soil type also needs to be investigated. Greater emphasis on the underlying processes driving changes in water repellency under elevated CO 2 , using approaches similar to those reported by Feeney et al (2004Feeney et al ( , 2006 and Hallett et al (2003), will be the subject of future research.…”
Section: Discussionmentioning
confidence: 94%
“…Several studies have found microbial and plant biomass influences the development of water repellency in soil (Feeney et al 2004;Feeney et al 2006;Hallett et al 2003). Under elevated atmospheric CO 2 , we hypothesise that an increase in plant biomass will drive an increase in water repellency, either directly or through secondary microbial processes.…”
Section: Introductionmentioning
confidence: 85%